Antimicrobial peptides in multiresistant respiratory infections - González-GarcÃa, Melaine; Ständker, Ludger; Otero-González, Anselmo Jesús (Revista Cubana de Medicina Tropical, 2018)
Antimicrobial peptides are small cationic molecules present in almost all living organisms. They show direct or indirect (immunomodulation) activity in a wide range of pathogenic microorganisms as members of the humoral arsenal of innate immunity. In mammals they play a significant role in respiratory airways. The most abundant antimicrobial peptides in the respiratory tract of mammals are lysozymes, lactoferrin, histatins, defensins and cathelicidins. Respiratory and pulmonary infections are combated, primarily, by antimicrobial peptides like LL-37 against Gram-negative bacteria, histatin 5 against Candida albicans and human peptides from neutrophils against adenovirus, influenza and parainfluenza. This paper provides a review of the most important antimicrobial peptides in the respiratory tract and their use in the search for new effective agents against microorganisms that cause respiratory infections based on information published in MedLine, the Web of Science and Scopus in recent years.